Rapid detection and typing of Staphylococcus aureus based on nanopore Cas9-targeted sequencing - PAN Shufan; YANG Donglei; WANG Pengfei (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2025)
Objective·To achieve the rapid detection of Staphylococcus aureus using nanopore Cas9-targeted sequencing (nCATS) technology, and simultaneously perform staphylococcal protein A (spa) typing and staphylococcal cassette chromosome mec (SCCmec) typing.Methods·The spa gene and SCCmec gene elements were selected as two regions of interest (ROIs) for targeted sequencing. Four types of CRISPR RNAs (crRNAs) were designed to form Cas9 ribonucleoproteins (RNPs) to cleave sequences flanking the two ROIs. For each crRNA, a 42 bp synthetic target DNA was designed. Appropriate crRNAs were screened, the cleavage system was optimized, and both the cleavage reaction time and Cas9 RNP synthesis temperature were determined based on the results of Cas9 RNP cleavage efficiency testing. Genomic DNA was extracted from a methicillin-resistant Staphylococcus aureus (MRSA) strain, and the ends flanking the cleaved ROIs were dephosphorylated and dA-tailed. Sequencing adapters were ligated, and sequencing was performed using a nanopore platform. The quality scores of the sequencing data were analyzed, and the obtained nucleic acid sequences were compared with those in the mecA, spa and SCCmec databases. Based on the comparison results, the presence of Staphylococcus aureus, MRSA or not, and spa and SCCmec types were determined.Results·Two sets of crRNAs were designed. Based on grayscale analysis of electrophoresis results, the set with higher cleavage efficiency was selected for further experiments. Optimization showed that a 1∶1 ratio of Cas9 RNP to target DNA, a 15 min cleavage reaction time, and a Cas9 RNP synthesis temperature of 25 ℃ yielded a cleavage efficiency of 87.41%. nCATS sequencing quality scores ranged between 15 (Q15) and 20 (Q20), indicating an approximate sequencing accuracy of 99%. Sequence comparisons with the mecA, spa and SCCmec databases revealed that the strain's spa type was t2 and its SCCmec type was Ⅱ. These results were consistent with those obtained by PCR amplification sequencing and multiplex PCR.Conclusion·The nCATS technique enables rapid detection of Staphylococcus aureus, while simultaneously providing spa and SCCmec typing information.